Risk factors for acute colonic pseudo‐obstruction after caesarean section: A retrospective case–control study. (11th July 2022) - Ford, Elisa; Bozin, Michael; Shedda, Susan; McCormick, Jacob; Skandarajah, Anita; Cade, Thomas
Abstract : Background: Pregnancy and caesarean section are known to predispose to the development of acute colonic pseudo‐obstruction (ACPO), a rare form of functional ileus of the distal large bowel. Pathogenesis of ACPO is likely influenced by pregnancy and childbirth and subsequent changes to hormonal, autonomic and metabolic physiology. Identifying pregnancy risk factors will assist with early identification, as the insidious onset postpartum often leads to delayed diagnosis and bowel ischaemia, perforation and sepsis. Aims: To establish pregnancy risk factors associated with the development of ACPO after caesarean section. Materials and Methods: A retrospective case–control study included 19 121 women undergoing caesarean between 1 January 2008 and 31 December 2016 at a tertiary referral hospital. Twenty‐three cases of computerised tomography (CT)‐diagnosed ACPO post‐caesarean were identified from hospital medical records and imaging databases. Controls were matched for gestational and maternal age within one week of delivery with a ratio of 1:3. Results: The incidence of ACPO was one in 800 caesarean sections. ACPO was significantly more likely to occur in women who had been administered opioid analgesia in labour (odds ratio (OR) 4.67, P = 0.04), and a trend for increased estimated blood loss (OR 1.01, P = 0.01). There was no increased risk associated with emergency or elective caesarean classification, previous abdominal surgery, type of anaesthesia, duration of labour, oxytocin augmentation, intrapartum fever, hypertensive disorders, diabetes in pregnancy, antepartum haemorrhage, multiple gestation, fetal presentation or birthweight. Conclusions: Risk factors for developing ACPO post‐caesarean include opioid analgesia in labour and a trend for increased blood loss.